The Digital Lifeline: AI Chatbots in Mental Health Crisis Intervention and Support - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The global mental health crisis presents a formidable challenge to traditional healthcare systems. Stigma, a shortage of trained professionals, and geographi...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Medical Ethics